Hubungan Resiliensi dengan Stres Lansia Penderita Hipertensi di Puskesmas Alang - Alang Lebar - Sandra Putra, Riko; Mutmainah, Mutmainah (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Resilience is an individual's ability to face pressure or difficulties, while stress is the body's response to pressure that can worsen hypertension in the elderly. This study aims to determine the relationship between resilience and stress levels in elderly people with hypertension at the Alang-Alang Lebar Community Health Center. This study used a quantitative approach with a cross-sectional analytical survey design. A sample of 91 elderly people was selected using a purposive sampling technique. The research instruments used included the Connor-Davidson Resilience Scale (CD-RISC) questionnaire to assess resilience and a modified Perceived Stress Scale questionnaire to measure stress levels. Data analysis was performed using the chi - square test. The results showed that most elderly people had high resilience (87.9%), while low resilience was found in a small proportion of elderly people (12.1%). The stress levels of elderly people were generally classified as mild to moderate, with mild stress in the majority of elderly people, followed by moderate stress, and a small proportion experiencing high stress. The test results showed a significant relationship between resilience and stress levels in elderly people with hypertension, with a p-value of 0.000, indicating that elderly people with high resilience tend to experience lower stress levels, while elderly people with low resilience tend to experience higher stress levels. Based on these findings, it is recommended that elderly people increase their resilience through positive activities, such as light exercise, hobbies, or social interactions. This research can also serve as a basis for further studies examining other factors that influence stress in elderly people with hypertension.